Identifikasi Kelimpahan Partikel Mikroplastik pada Gula Pasir di Indonesia - sincihu, yudhiakuari; Morina, Shella; Sudewi, Ni Putu; Mulyasari, Tri Marthy; Ningrum, Prehatin Trirahayu; Steven; Dewi, Dewa Ayu Liona (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
Microplastics (plastic particles <5 millimeters in diameter) have become a novel food contaminant for humans.Microplastics was estimated that children consume 106-113 microplastics per day and 126-142 particles in adults.The main prevention effort is to identify the presence of plastic particles in food, one of which is sugar. Microplasticsthat are in the digestive tract can enter the bloodstream and distributed to other parts of the body. These particlescannot be destroyed by the body's cellular mechanisms, thus triggering inflammation, genotoxicity, hypersensitivity,oxidative stress, and cell death. The aim of the study was to measure the number of particles, shape and diameter ofplastic particles as contaminants in refined sugar produced in Indonesia. Quantitative descriptive research using 16sugar brands that are produced, known and widely consumed in Indonesia. The research was carried out at theClinical Pathology Laboratory, Widya Mandala Surabaya Catholic University. Quantification of the number, shapeand diameter of plastic particles using a microscope. The examination results showed that all sugar samples containedplastic particles between 5-100 MPs/50 gram of sugar, most of the contaminants were in the form of pellets, and thelargest particle diameter was 367µm.